Territorial Cleansing: A Geopolitical Approach to Understanding Mass Violence. Issue 3 (2nd July 2016) - Egbert, Stephen L.; Pickett, Nathaniel R.; Reiz, Nicole; Price, William; Thelen, Austen; Artman, Vincent
Abstract: The 'geopolitical where' of genocide and mass violence has been understudied, under-theorized, and underappreciated, particularly by those outside geography. We examine the study of genocide and mass violence with a critical geographic lens and propose a framework, territorial cleansing, that places such events within an idealized territorial conceptualization. We define territorial cleansing as a geopolitical project consisting of processes, policies, and actions designed by an in-group to remove an Othered group from a territory, where removal may mean physical expulsion or death but may include a range of other means, including 'removal in place' by such measures as coerced assimilation or suppression of group identity. The process begins with the in-group's formulation of an imagined place that is idealized and valorized. An environment is then created that allows for the removal of the undesired element and the realization of the imagined place. Once the undesirable Others are identified and conditions are created to facilitate their removal, legal, social, or physical actions might be taken to cleanse the territory of this element. A key feature of the territorial cleansing framework is that it is almost infinitely scalable in both space and time as well as along a continuum of violence.